2021
DOI: 10.3389/fpsyg.2020.612889
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on the Dairy Product Consumers’ Intention to Adopt the Food Traceability’s Technology: Push-Pull-Mooring Model Integrated by D&M ISS Model and TPB With ITM

Abstract: Against the backdrop of frequent food safety problems, the importance of establishing food traceability systems has become increasingly important and urgent to address the contradiction between consumer information on safe food choices and the proliferation of problematic foods. The purpose of this study is to empirically study the influencing factors of Chinese consumers on the food traceability system in the food safety field (hereinafter referred to as FTS). In this study, multiple models—push factor (infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…More importantly, our findings show that trust in BFTS is the only trust type exerts an outstanding predictive ability on intention to purchase organic products. H8, which is supported by the above analysis results, is in consistent with the previous studies [54,[86][87][88][89].…”
Section: Discussionsupporting
confidence: 92%
“…More importantly, our findings show that trust in BFTS is the only trust type exerts an outstanding predictive ability on intention to purchase organic products. H8, which is supported by the above analysis results, is in consistent with the previous studies [54,[86][87][88][89].…”
Section: Discussionsupporting
confidence: 92%
“…Second, this study proposed a more comprehensive integrated framework that was combined with ITM (Kim and Prabhakar, 2004 ) and UTAUT2 (Venkatesh et al, 2012 ) to confirm influencing factors that facilitated the initial trust, while examining the technology of the user terminal characteristics and the initial trust's influence on usage intention. According to the results of this research, it is concluded that the combined model provides a stronger interpretation on adoption willingness than UTAUT2 and ITM, separately, which is consistent with previous studies (Lin et al, 2019 , 2022 ; Lin and Wu, 2021 ; Lin X. C. et al, 2021 ; Lin X. et al, 2021 ). Compared with the single-model analysis, this two-dimensional combined framework can comprehensively confirm the factors that positively influence the usage intention of digital currency's technology.…”
Section: Discussionsupporting
confidence: 91%
“…Subjective norms mainly examine the social influence on an individual's behavior like desire for gaining popularity, status and acceptance (Kordi Ghasrodashti, 2018). Lin and Wu (2021) corroborate that subjective norms strongly influence consumers' switching intentions. Subjective norms have a significant impact on consumers' adoption of sharing accommodation services (Muñoz-Leiva et al, 2018).…”
Section: Mooring Factorsmentioning
confidence: 75%